2023
DOI: 10.1111/ele.14200
|View full text |Cite
|
Sign up to set email alerts
|

Altered wing phenotypes of captive‐bred migratory birds lower post‐release fitness

Abstract: Captive breeding and release to the wild is a globally important conservation tool. However, captivity can result in phenotypic changes that incur post‐release fitness costs, especially if they affect strenuous or risky behaviours. Bird wing shape is critical for migration success and suboptimal phenotypes are strongly selected against. In this study, I demonstrate surprising plasticity of bird wing phenotypes in captivity for 4/16 studied species. In a model species, captive‐born juveniles with wild wing phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Strong differences in behaviour between captive‐bred and wild individuals (e.g., lack of exposure to natural stimuli, use of food resources, movement pattern, and/or differences in social structure) could make it difficult for captive‐bred birds to successfully integrate and mate with wild populations (Crates et al., 2023 ). Accordingly, poor performance of captive‐bred individuals after their release into the wild has been well documented in mallards (Champagnon, Elmberg, et al., 2012 ; Champagnon, Guillemain, et al., 2012 ; Söderquist et al., 2017 ) and other birds (Stojanovic, 2023 ). For marbled teal, GPS tagging has shown that captive‐bred birds have higher mortality and lower mobility than wild birds after their release, and has provided little evidence that they can breed successfully (Pérez‐García et al., in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong differences in behaviour between captive‐bred and wild individuals (e.g., lack of exposure to natural stimuli, use of food resources, movement pattern, and/or differences in social structure) could make it difficult for captive‐bred birds to successfully integrate and mate with wild populations (Crates et al., 2023 ). Accordingly, poor performance of captive‐bred individuals after their release into the wild has been well documented in mallards (Champagnon, Elmberg, et al., 2012 ; Champagnon, Guillemain, et al., 2012 ; Söderquist et al., 2017 ) and other birds (Stojanovic, 2023 ). For marbled teal, GPS tagging has shown that captive‐bred birds have higher mortality and lower mobility than wild birds after their release, and has provided little evidence that they can breed successfully (Pérez‐García et al., in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the evolutionary history of behaviour when designing an enclosure or when writing management guidelines for a zoo-housed species builds ecological relevance into the environment created for the species, and this enables a behaviour's adaptive potential to be conserved. For example, morphological [119,120] and behavioural [121,122] differences are known to occur between free-living and captive-bred individuals of different species. Such changes to morphology and behaviour would compromise wild survival and reproductive potential.…”
Section: Population Management and Translocationmentioning
confidence: 99%
“…However, how these effects play out within rather than between species is not yet clear. It is also important to acknowledge that other morphological changes can affect survival (for example wing shape in orange-bellied parrots, Neophema chrysogaster ; [ 72 ]) making it difficult to isolate the effect of morphological changes to the brain from morphological changes to the body.…”
Section: The Captive Brainmentioning
confidence: 99%